Blood Pressure Responses During Exercise Were Associated With Average Home Blood Pressure and Home Blood Pressure Variability: The Electronic Framingham Heart Study - Xuzhi Wang; Yuankai Zhang; Chathurangi H. Pathiravasan; Nicole L. Spartano; Emelia J. Benjamin; David D. McManus; Gregory D. Lewis; Martin G. Larson; Ramachandran S. Vasan; Joanne M. Murabito; Chunyu Liu; Matthew Nayor (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Abnormal exercise blood pressure (BP) responses are associated with hypertension and cardiovascular disease, but their relationship with home BP over a mid‐ to long‐term time span is unknown. Methods At an FHS (Framingham Heart Study) research examination (2016–2019), participants underwent maximum incremental ramp cycle ergometry cardiopulmonary exercise testing with BP measured every 2 minutes. At the same exam, English‐speaking participants enrolled in the electronic FHS with an iPhone were provided with a digital BP cuff to measure home BP weekly for 1 year. Linear regression models examined associations of exercise BP with average home systolic BP (SBP), home‐based hypertension, and week‐to‐week average real variability of home SBP, over 1‐year follow‐up. Participants with <3 weeks of BP return were excluded. Results Among 808 participants (mean age, 53 years; 58% women; 92% White individuals; 47% hypertension), higher exercise BP responses (peak SBP, SBP at 75 W, SBP/workload slope, peak diastolic BP, and diastolic BP at 75 W) were associated with higher average home SBP. Higher peak diastolic BP was associated with a greater risk for home hypertension. Additionally, higher SBP/workload slope and peak diastolic BP were associated with elevated average real variability of home SBP only in participants without antihypertensive use. Conclusions Higher exercise BP responses were associated with higher average home‐based BP, greater home‐based hypertension risk, and increased home‐based BP variability over a mid‐ to long‐term time span. However, these associations may vary by antihypertensive medication use. Exercise BP may play an important role in hypertension prevention and treatment.